PENYAKIT PEMBUSUKAN KAKI (FOOT ROOT) INFEKSI BAKTERIAL JARINGAN LUNAK PADA SAPI DAN DOMBA - I Gusti Agung Ayu Komang Ratih Wirawan; Safta Arga Yanuar; Augusta Audriansyah Puteri (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Foot root is caused by bacterial infections, especially Fusobacterium necrophorum and Dichelobacter nodosus, which cause swelling and lesions in the interdigital area, leading to lameness in the interdigital area, thus negatively impacting livestock productivity and welfare. Research results show that the prevalence of foot rot is higher in sheep than in cattle. The main clinical symptoms observed include swelling, redness, erosion, and necrosis (decay) of the hoof tissue and interdigital area, which causes the animal to experience severe lameness. These risk factors indicate humid environmental conditions and poor barn sanitation.